Introducing Cryptographic and Sorting Algorithms to Primary School Students and its Effect in the Classroom - Karakostas, Athanasios; Vlachou, Akrivi (IEEE Global Engineering Education Conference, 2024)
In this paper, we focus on primary school students and show that it is possible for students without prior knowledge in these areas to re-invent and successfully implement cryptogra-phy and sorting algorithms, as well as the effect of these activities to the students' eagerness to engage with other computer science-related subjects. To this end, we developed appropriate activities to introduce cryptography and sorting algorithms and carried out in the classroom to primary school students of the Greek education system. During our research, we conducted an in-class cross-evaluation in three phases of the proposed approach, using two groups of students of different age groups and different starting subject, cross- referencing their results at the end of the third phase. These groups had no previous contact with the subject of cryptography or sorting algorithms, but had previous experience with programming and the use of data structures through our past work. Our results show that our approach managed to successfully introduce sorting and cryptography algorithms in primary education and to stimulate the interest of the majority of the students, while helping them to more optimistically face additional new areas of computer science.